Pagtatagpo sa kabilang dulo panitikang testimonial ng desaparecidos - Batnag, Aurora E.; Mercado, Emil; Padilla, Jennifer T.; Amado V. Hernandez Resource Center ([Manila?] Raintree Publishing, 2009)
Collection of poems, letters and testimonials of the families of victims of enforced disappearances.
In Tagalog, some in English
Keywords: Disappeared persons -- Philippines; Political persecution -- Philippines; Human rights -- Philippines; Victims of crimes -- Philippines